Evaluating impacts of University Cooperation for Development from the Voice of the South - María José Vázquez de Francisco; Mercedes Torres Jiménez; Pedro Caldentey del Pozo; Olexandr Nekhay (Revista de Economía Mundial, 2017)
University Cooperation for Development is an important part of the “third mission” of universities. From a capability approach, this study investigates the perception that Latin-American university teachers, researchers and staff have as recipients of aid, about the effects of long-term university cooperation programmes with universities from the North. Using a combination of qualitative (Colaizzi) and quantitative (Analytic Hierarchy Process) methods, an assessment of university cooperation activities was obtained, and a categorisation and prioritisation of impacts was found. This impact evaluation could provide an orientation for future more effective programmes of university cooperation, from the point of view of aid recipients.